Triethylammonium halochromates/silica gel: an efficient reagent for oxidative coupling of thiols to disulfides - Shahriare Ghammamy; Mohammad Kazem Mohammadi; Ali Hassani Joshaghani (Macedonian Journal of Chemistry and Chemical Engineering, 2008)
Triethylammonium halochromates, (C2H5)3NCrO3X, TEAXC (X = Cl, F) are easily synthesized by the reaction of triethylamine with a solution of chromium(VI) oxide in 6M hydrochloric acid, or a solution of chromium(VI) oxide in 40% hydrofluoric acid. These reagents are easily supported on common silica gel and can be used as heterogeneous oxidants. Triethylammonium halochromate(VI) is a versatile reagent for the effective and selective oxidation of organic substrates. Various aliphatic (cyclic and acyclic) and aromatic thiols are converted into the corresponding disulfides by treatment with triethylammonium fluorochromate(VI), (TEACC) or triethylammonium chlorochromate(VI), (TEAFC) supported on silica gel, in excellent yields and under mild reaction conditions.